Atrial Myxoma - A Dramatic Tale! - Harris, Elizabeth (Operating Room Nurses Association of Canada Journal, 1991)
Having a spare moment on Wednesday, her day off, Mrs. B. dropped in for her echocardiogram. She had no idea of the sharp curve the course of her life was about to take.